Comparison of Meniscal Tear Location and Zone in Athletes: A Systematic Review of Implications for Return to Sport - I Nyoman Gede Witriadnyana; I Wayan Subawa; I Gede Mahardika Putra (International Medical Journal Corp. Ltd, 2025)
Introduction: Meniscal injury represents one of the most prevalent knee injuries observed in the athletic population, carrying a substantial risk of threatening career longevity. The selection between the two primary management strategies—partial meniscectomy or meniscal repair—presents a critical clinical dilemma, balancing the need for rapid recovery against the imperative of preserving long-term joint health. The specific characteristics of the tear, including its anatomical location (medial versus lateral) and its vascularization zone, are recognized as major determinants influencing the final functional outcome. Methods: This systematic review was rigorously executed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. A comprehensive literature search was performed across major electronic databases, including PubMed, Semantic Scholar, Springer, and Google Scholar. The search utilized a detailed set of Boolean keywords targeting the athlete population, meniscal repair interventions, comparisons with meniscectomy and tear location, and return-to-sport outcomes. Following the screening of 6,756 initial records, a total of 32 eligible studies were ultimately included in the final analysis. These studies involved athletes with arthroscopically or radiologically confirmed meniscal tears, explicitly reported recovery outcomes, and utilized appropriate study designs. Results: The findings demonstrate a clear difference in recovery timelines: Meniscectomy consistently enabled athletes to achieve a faster return to sport (RTS), typically within 1 to 4.3 months, compared to the longer duration required for meniscal repair (5.6–7.6 months). Despite this variance in timing, the overall return-to-sport rate was generally comparable between the two procedures, consistently falling within the range of 77% to 93%. Repair of the lateral meniscus is clinically favored due to its inherently superior healing potential. Conversely, the rate of repair failure exhibited significant variation contingent on the tear morphology, reaching up to 27.4% for specific patterns such as bucket-handle tears. The rates at which athletes successfully returned to their pre-injury performance level were broadly distributed (53.9% to 92.6%) and tended to be lower following complex interventions, such as meniscal allograft transplantation. Discussion: The evidence highlights a fundamental trade-off: the rapid functional recovery afforded by meniscectomy contrasts sharply with the long-term joint preservation advantages provided by meniscal repair. The optimal treatment strategy requires meticulous individualization, demanding careful consideration of the specific tear location (with repair strongly advocated for the lateral meniscus), the tear pattern, the athlete’s age, and their professional activity level. Furthermore, the systematic review established that accelerated rehabilitation protocols do not correlate with an increased risk of repair failure, thereby supporting the implementation of earlier functional recovery programs. Conclusion: The clinical management of meniscal tears in athletes should prioritize tissue preservation through meniscal repair whenever technically feasible, particularly in the context of lateral tears and for young athletes. Although this preservation approach mandates a longer period of rehabilitation, it constitutes a vital investment in the athlete’s long-term joint health and the sustainability of their athletic career.